TELEVISION MEDIA'S ROLE IN AGENDA-SETTING TO EDUCATE YOUNG VOTERS FOR THE 2024 INDONESIAN GENERAL ELECTIONS - Dwi Firmansyah; Alifiah Ghaniyyu Widyaningrum; Donny Kurniawan (Perspektif Komunikasi Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2025)
Indonesia is experiencing a demographic bonus with a surge of young voters, offering significant potential for political change through fresh perspectives. One common assumption is that the younger generation is apathetic toward politics, yet this view is questionable given their potential impact. Television media, as a public broadcasting institution, plays a vital role in disseminating political information, especially in the lead-up to the 2024 general elections. In the era of media convergence, television news can educate the public not only via traditional broadcasts but also through content shared on social media platforms. SCTV, a major Indonesian television network, utilizes an infographic-based program “Kamu Harus Tau” (“You Must Know”) to educate first-time and young voters. This study is framed by the agenda-setting theory. Data were collected through in-depth interviews with key informants – including the Executive Producer of Liputan 6 Pagi and the Producer/Presenter of “Kamu Harus Tau” – and through content analysis of the program’s broadcasts on television and online. Findings indicate that “Kamu Harus Tau” effectively enhances young voters’ understanding of the electoral process and encourages greater participation in the 2024 general election. The program demonstrates how mass media can direct public attention to election-related issues (agenda-setting), thereby influencing public perceptions and knowledge. The study offers a novel perspective by examining a televised infographic program that bridges traditional media and social media to educate young voters, highlighting theoretical and practical implications for voter education initiatives.